Asymmetric T-cell division: insights from cutting-edge experimental techniques and implications for immunotherapy - Kaminskiy, Yaroslav; Ganeeva, Irina; Chasov, Vitaly; Kudriaeva, Anna; Bulatov, Emil (Frontiers in Immunology, 2024)
Asymmetric cell division is a fundamental process conserved throughout evolution, employed by both prokaryotic and eukaryotic organisms. Its significance lies in its ability to govern cell fate and facilitate the generation of diverse cell types. Therefore, attaining a detailed mechanistic understanding of ACD becomes essential for unravelling the complexities of cell fate determination in both healthy and pathological conditions. Yet, the role of asymmetric division in T cell biology has only recently been unveiled. Here we provide an overview of the T cell asymmetric division field with the particular emphasis on experimental methods and models with the aim to guide the researchers in the selection of appropriate in vitro/in vivo models to study asymmetric division in T cells. We present a comprehensive investigation into the mechanisms governing the asymmetric division in various T cell subsets underscoring the importance of the asymmetry in fate-determining factors segregation and transcriptional and epigenetic regulation. Furthermore, the intricate interplay of TCR signalling and the asymmetric division geometry is explored, shedding light on the spatial organization and the impact on cellular fate.